2019
DOI: 10.3847/1538-3881/ab0e0a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-short-period Planets from Secular Chaos

Abstract: Over a hundred rocky planets orbiting Sun-like stars in very short orbital periods ( 1 day) have been discovered by the Kepler mission. These planets, known as ultra-short-period (USP) planets, are unlikely to have formed locally, or have attained their current orbits when their birth protoplanetary disks were still present. Instead, they must have migrated in later in life. Here we propose that these planets reach their current orbits by high-eccentricity migration. In a scaled-down version of the dynamics th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 97 publications
(98 reference statements)
2
83
0
Order By: Relevance
“…This is consistent with the observed trend that when one member of an adjacent pair of planets has an orbital period less than a day, the period ratio is unusually large (Steffen & Farr 2013;Sanchis-Ojeda et al 2014;Steffen & Coughlin 2016). The origin of the ultrashort-period planets remains unknown (Winn et al 2018) though a number of hypotheses have been proposed ranging from stripped cores of giant planets (Valsecchi et al 2014;Königl et al 2017) to various dynamical effects coupled with stellar tides (Muñoz et al 2016;Lee & Chiang 2017;Pu & Lai 2019;Petrovich et al 2019). The nearby presence of additional small planets would seem not to support the stripped-cores possibility, since hot Jupiter planets tend to be alone with few exceptions (Wright et al 2009;Steffen et al 2012;Becker et al 2015).…”
Section: Dynamical Stability and System Architecturesupporting
confidence: 85%
“…This is consistent with the observed trend that when one member of an adjacent pair of planets has an orbital period less than a day, the period ratio is unusually large (Steffen & Farr 2013;Sanchis-Ojeda et al 2014;Steffen & Coughlin 2016). The origin of the ultrashort-period planets remains unknown (Winn et al 2018) though a number of hypotheses have been proposed ranging from stripped cores of giant planets (Valsecchi et al 2014;Königl et al 2017) to various dynamical effects coupled with stellar tides (Muñoz et al 2016;Lee & Chiang 2017;Pu & Lai 2019;Petrovich et al 2019). The nearby presence of additional small planets would seem not to support the stripped-cores possibility, since hot Jupiter planets tend to be alone with few exceptions (Wright et al 2009;Steffen et al 2012;Becker et al 2015).…”
Section: Dynamical Stability and System Architecturesupporting
confidence: 85%
“…3. Petrovich et al investigated the possibility of eccentricity excitation from secular dynamical chaos in compact multiplanet systems [93]. They predicted that USP planets would often be accompanied by outer planets extending out to 1 AU.…”
Section: Formation Theoriesmentioning
confidence: 99%
“…Dynamical migration mechanisms due to planetary interactions may also contribute to the large mutual inclinations of USPs close to the host stars (Petrovich et al 2019;Pu & Lai 2019). The J 2 precession timescales of the USPs are around 10 4 yrs, and thus, the transit duration variations are too small to be detected to distinguish the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that a large mutual inclination is also associated with a larger orbital period ratio between USP and its neighboring planets. It has been shown that dynamical hotter formation scenarios can generate orbital migration and mutual inclination of USPs simultaneously, and explain the observed signatures (Petrovich et al 2019;Pu & Lai 2019).…”
Section: Introductionmentioning
confidence: 94%